INCREASE OF EFFICIENCY COMPLEX TREATMENT OF PARODENTIUM DISEASES IN HAEMATOLOGICAL PATIENTS - Alkishiev, K.S.; Mamedov, F.J.; Safarov, A.M. (World of Medicine and Biology, 2013)
Data of complex stomatologic inspection and results of treatment 45 гематологических patients with inflammatory parodоntium diseases (IPD) (at the age from 15 till 25 years) have been analysed. In the clinical block the estimation of efficiency of use in complex treatment of patients with IPD a domestic preparation of "Solident" representing the multicomponent liquid medicinal form is spent. As a result of research it is established that drug possesses expressed antiinflammatory and antiseptic actions and is one of optimum and highly effective treatment-and-prophylactic means in treatment of gingivitis and periodontitis easy degree in patients, suffering anemia.
Keywords: gingivitis; periodontitis; an anaemia; therapeutic agent